How AI is Changing Healthcare: A Review of Innovations and Challenges in Health Informatics - Ghozali, Muhammad Thesa (Dinasti Research, 2024)
Revolutionizing healthcare with better, quicker diagnoses, more refined treatment plans, enhanced patient monitoring, and still faster administrative process. This transformation is exemplified in the AI technology of health informatics, with tools helping analyze huge datasets, extract patterns, and improve clinical decisions. This article contemplates the multifarious ways AI has revolutionized healthcare, the innovations falling in the area of diagnostics, treatment personalization, remote care, and operational effectiveness. Nonetheless challenges becoming evident consist of ethical concerns with data privacy issues and limiting the actual application of these models. A mixed-method approach was utilized to evaluate some examples of evolving inventions. From the available evidence presented in articles of this nature, compiled from the various other clinical trials undertaken on AI-based health information systems and AI-driven research projects, concrete examples of AI solutions that work in real-time in radiology, pathology, virtual health assistants and predictive analytics have been proven to be effective. The review, however, discusses struggles regarding regulatory compliance, algorithmic bias, and clinician adoption. The review calls for stronger policy frameworks, more interdisciplinary collaboration, and continuous research to bolster the uptake of AI in clinical workflows by overcoming these challenges. The future of AI's transformational climax in the healthcare sector depends upon the responsible and equitable use of these powerful technologies.